OBSERVATIONS ON THE BREEDING AND LARVAL DEVELOPMENT OF CHILKA ’SAHAL’ ELEUTHERONEMA TETRADACTYLUM (SHAW) - Kowtal, G V (Indian Journal of Fisheries, 2011)
Eleutheronema tetradactylum (Shaw) breeds in the Chilka Lake in the northern zone in the Tua Nali area during January-June period as evidenced by the collection of eggs and larvae and mature and spent specimens. On the west coast of India it has two spawning seasons, one in January-April and the other in July-September. The Chilka ’sahal’ possibly undertakes movements from lake to sea for the second spawning season in July-September